2005
DOI: 10.1007/s11031-005-7954-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Approach and Avoidance Cues on Attentional Flexibility

Abstract: In two experiments, we tested the prediction that rudimentary approach, relative to avoidance, motivational cues bolster attentional flexibility. This prediction was assessed using manipulations of both exteroceptive and interoceptive motivational cues and with two different measures of attentional flexibility, the Stroop task and the 2-back task. Results were consistent with predictions, suggesting that approach, relative to avoidance, motivational cues facilitate task performance by enhancing the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 33 publications
7
70
0
Order By: Relevance
“…A maze task developed by Friedman and Förster (2005a;see also: Krpan & Schnall, 2014) was used to induce motivational orientation through cognitive activation of approach and avoidance behaviors, and valenced photographs were selected from the International Affective Picture System (IAPS; Lang et al, 2005). The photographs were used because Gable and Harmon-Jones (2008) suggested that appetitive positive stimuli (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A maze task developed by Friedman and Förster (2005a;see also: Krpan & Schnall, 2014) was used to induce motivational orientation through cognitive activation of approach and avoidance behaviors, and valenced photographs were selected from the International Affective Picture System (IAPS; Lang et al, 2005). The photographs were used because Gable and Harmon-Jones (2008) suggested that appetitive positive stimuli (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Wells & Petty, 1980;Strack, Martin, & Stepper, 1988;Duclos et al, 1989;Cacioppo et al, 1993;Stepper & Strack, 1993;Förster & Strack, 1996, Friedman, & Förster, 2002, 2005aCenterbar & Clore, 2006). Indeed, the compatibility hypothesis further suggests that evoking valence-compatible motivational orientation facilitates how people process and respond to valenced stimuli compared to incompatibility (e.g.…”
Section: Too Close For Comfort: Stimulus Valence Moderates the Influementioning
confidence: 99%
“…In Studies 1 and 4, participants will be induced into an approach or an avoidance motivation orientation by assuming a certain arm position (Cacioppo, Priester, & Berntson, 1993; Förster & Strack, 1997, 1998; Neumann & Strack, 2000; Priester, Cacioppo, & Petty, 1996). In Studies 2 and 3, participants will, instead, solve an approach or an avoidance maze (Friedman & Förster, 2001, 2005). …”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…An approach orientation was activated by having participants lead the mouse to a piece of cheese lying at the exit, and an avoidance orientation was activated by having them to lead the mouse to the mouse-hole, in order to escape the danger of an owl hovering over the maze (Friedman & Förster, 2001, 2005). Immediately after solving the maze, participants completed the Twenty Statements Task.…”
Section: Study 2: Approach/avoidance Cues and Self-construalmentioning
confidence: 99%
“…Several studies have examined the influence on cognitive performance caused by manipulations of promotion and prevention cues in different contexts (e.g., Friedman & Förster, 2001;Roese, Hur, & Pennington, 1999;Seibt & Förster, 2004). Among others, an influence of cognitive performance caused by manipulations of promotion or prevention cues has been documented for attention-related tasks (e.g., Derryberry & Tucker, 1994;Easterbrook, 1959;Friedman & Förster, 2005). Different research provides evidence that a prevention motivation results in better performance on detail-oriented tasks, whereas a promotion motivation results in better performance on global-oriented tasks (Derryberry & Reed, 1998;Förster & Higgins, 2005;Förster et al, 2006).…”
Section: Studymentioning
confidence: 99%